Dynamic Pricing Under Debt: Spiraling Distortions and Efficiency Losses - Besbes, Omar; Iancu, Dan A.; Trichakis, Nikolaos (Management Science, 2018)
Firms often finance their inventory through debt and subsequently sell it to generate profits and service the debt. Pricing of products is consequently driven by inventory and debt servicing considerations. We show that limited liability under debt induces sellers to charge higher prices and to discount products at a slower pace. We find that these distortions result in revenue losses that compound over time, leading to some form of performance spiral down. We quantify the extent to which these inefficiencies can be mitigated by practical debt contract terms that emerge as natural remedies from our analysis, and find debt amortization or financial covenants to be the most effective, followed by debt relief and early repayment options. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2862 . This paper was accepted by Serguei Netessine, operations management.